RPOA Norm Localization for Indonesia in Handling IUU Fishing - Arimadonna, Arimadonna (Indonesian Journal of International Law, 2020)
The success of the Indonesian Maritime Policy cannot be separated from Indonesia’s own role, which initiated the establishment of RPOA-IUU Fishing. Global IUU Fishing securitization has led to the localization of anti-IUU fishing in the region and domestic. As a recognized global norm in the Southeast Asia region, IUU Fishing is known to have an impact on comprehensive security in the Southeast Asian region so that a regional regime is formed to fight IUU Fishing. This research aims to find out why norm localization takes place in some countries but not in others such as Vietnam, Thailand, and Laos. What kind of urgency needs more attention from these countries which not comply, than ratifying the anti-IUU fishing norms in each country’s NPOA on IUU Fishing? A qualitative methodology is pursued in this article to identify the formation of official documents. Specifically, discourse analysis is utilized to help understand the intentions of actors through constructive analysis of social phenomena in the obtained documents. There are some important findings due to this research, such as different level of urgency in countries, not all neighbour countries of Indonesia find it important to Norm Localized IUU Fishing.